Social medias and the spread of hoaxes: perception of secondary students - Felizardo Dos Santos, Silvia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Connectivity has changed our way of receiving information, transforming consumers into receivers and transmitters at the same time. This new model facilitates access to data that was previously restricted to only a few groups and also contributes to giving voice to minority and underrepresented social groups. Despite the positive aspects, disinformation has been gaining space and expanding spaces for manipulation among citizens. In this way, literacy is necessary for the development of critical thinking that allows us to face this situation. This study aims to shed light on the situation of education in a context of health crisis in schools in the community of Madrid.